2022
DOI: 10.1002/app.52224
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of phosphazene‐triazine bi‐base sulfonate and its applications in flame‐retardant modified polycarbonate

Abstract: A phosphazene‐triazine bi‐base sulfonate compound (CPNS) was synthesized using hexachlorocyclotriphosphazene, cyanuric chloride, and sodium p‐hydroxybenzene sulfonate as raw materials. The chemical structure was determined by FTIR, 1H NMR 31P NMR (NMR stands for nuclear magnetic resonance), and elemental analysis of P, Na. To study the flame retardant properties of CPNS, a series of modified polycarbonate (MPC) with different ratios of CPNS were prepared. The flame retardant performance and thermal stability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…When 0.04 wt % HSPP was added, the T onset of PC/HSPP-2 declined to 467 °C, while pristine PC had a T onset of 489 °C. This was because the organosulfonate groups in HSPP could promote chain isomerization and rearrangement of PC in high temperature. , A similar trend was also found for T max . Although the thermal stability of PC/HSPP composites decreased to some extent, the sulfonate moieties from HSPP could catalyze the isomerization and Fries rearrangement of PC and promote the formation of intermediate chars at a lower temperature, which favored the self-extinguishment of flame. ,, The final char residues at 700 °C for PC/HSPP were almost the same as those of PC due to the low loading of HSPP (less than 0.06 wt %), which suggested that the char forming effect could not play a dominant role in the following flame retardancy behaviors.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…When 0.04 wt % HSPP was added, the T onset of PC/HSPP-2 declined to 467 °C, while pristine PC had a T onset of 489 °C. This was because the organosulfonate groups in HSPP could promote chain isomerization and rearrangement of PC in high temperature. , A similar trend was also found for T max . Although the thermal stability of PC/HSPP composites decreased to some extent, the sulfonate moieties from HSPP could catalyze the isomerization and Fries rearrangement of PC and promote the formation of intermediate chars at a lower temperature, which favored the self-extinguishment of flame. ,, The final char residues at 700 °C for PC/HSPP were almost the same as those of PC due to the low loading of HSPP (less than 0.06 wt %), which suggested that the char forming effect could not play a dominant role in the following flame retardancy behaviors.…”
Section: Resultssupporting
confidence: 66%
“…With the temperature increasing, the residual phosphazene moieties began to degrade at temperature from ca. 520 to 620 °C, which resulted in the following second mass loss . Interestingly, although the final residues were almost the same, the first mass loss of HSPP in air was lower than that in N 2 , which could be caused by the oxidative scission of sulfonate groups …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations